The Correlation of Parity and Premature Rupture of Amnius - Noviana, Ekki; Munah, Fauzul; Oktaviasary, Windy (Journal of Ners and Midwifery, 2024)
Premature Rupture of Membranes (PROM) is a condition where the amniotic membranes rupture before delivery. Under normal circumstances 8-10% of preterm pregnant women will experience PROM. One of the contributors to AKI is the incidence of infection where this infection is caused by PROM. Term pregnant women under normal circumstances 8 – 10% will experience PROM. Preterm PROM occurs in 1% of pregnancies. PROM is more common in multiparous and grand multiparas due to excessive uterine motility, reduced cervical flexibility. The aim of the research was to determine the correlation between parity and the incidence of premature rupture of membranes at UMMI Hospital, Bogor City in 2023. This research used a cross sectional correlation design with medical record data as the data source. The samples were all mothers who gave birth with premature rupture of membranes. The measurement results were analyzed using the Chi Square test. The Chi square statistical test shows a value of p = 0.018 (p < 0.05), so Ha is accepted or Ho is rejected. There was a correlation between parity and the incidence of premature rupture of membranes. Further research can elaborate the trigger variables occurrence of PROM. This data can be used as primary data to obtain more results complete, accurate and valid.